Validação do roteiro de entrevista de Habilidades Sociais Educativas Parentais (RE-HSE-P) - Loureiro, Sonia Regina; Bolsoni-Silva, Alessandra Turini [UNESP] (My University, 2010)
The study of the parental educative social skills is extremely important for promoting the development and learning of children within interactive situations. The objective of this study was to assess reliability and validity of the Parental Educative Social Skills Interview Script (RE-HSE-P). It was proceeded: a) the test-retest reliability assessment, with a sample of 41 participants assessed in two distinct moments, with an interval of two months and the Cronbach's alpha was calculated; b) 213 parents of preschoolers (n =114) and school age children (n = 98) evaluated their children,were assessed for the construct and discrimination validity studies, differentiated in groups: a) demand for psychological intervention x community children without problems and b) children with behavior problems x children without behavior problems. The results showed satisfactory values of internal consistency and validity; besides, the factorial analysis pointed a unifactorial structure called positive parent-child interaction

O estudo das habilidades sociais educativas parentais se reveste de importância por promoverem o desenvolvimento e a aprendizagem dos filhos nas situações de interação. Objetiva-se testar as propriedades psicométricas de validade e fidedignidade do instrumento Roteiro de Entrevista de Habilidades Sociais Educativas Parentais. Procedeu-se: a) a avaliação da fidedignidade teste-reteste, tendo como amostra 41 participantes avaliados em dois momentos, com um intervalo de dois meses e ao cálculo do alfa de Cronbach; b) aos estudos de validade de constructo e discriminativa com 213 pais de crianças em idade pré-escolar (n = 114) e do ensino fundamental (n = 98), diferenciados em grupos: a) procura por atendimento x crianças da comunidade sem problemas, e b) crianças com problemas de comportamento x crianças sem problemas. Os resultados indicaram valores satisfatórios de consistência interna e de validade e a análise fatorial apontou uma estrutura composta por dois fatores: interação positiva pais-filhos e interação negativa pais-filhos.
Keywords: Validity; Social skills; Educative parental practices; Validade; Habilidades sociais; Práticas educativas parentais